2002
DOI: 10.1029/2001jd000410
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a biomass‐burning plume: Comparison of model results with observations

Abstract: [1] We have simulated the dynamical evolution of the plume from a prescribed biomass fire, using the active tracer high-resolution atmospheric model (ATHAM). Initialization parameters were set to reflect the conditions during the fire. The model results are compared with airborne remote-sensing and in situ measurements of the plume. ATHAM reproduces the injection height (250 -600 m) and the horizontal extent of the plume ($4 km) with good accuracy. The aerosol mass concentrations are underestimated but still i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 46 publications
6
102
1
Order By: Relevance
“…This is consistent with Trentmann et al [2002] where the authors estimated a total energy emission of about 5500 MW during the flaming phase for a 19.4 ha prescribed forest fire in the United States, giving a mean of 28 kW m…”
Section: à2supporting
confidence: 87%
“…This is consistent with Trentmann et al [2002] where the authors estimated a total energy emission of about 5500 MW during the flaming phase for a 19.4 ha prescribed forest fire in the United States, giving a mean of 28 kW m…”
Section: à2supporting
confidence: 87%
“…These mechanisms have been implemented and examined in several highresolution modeling studies (e.g. Luderer et al, 2006;Trentmann et al, 2002Trentmann et al, , 2006, which showed strong sensitivity of the pyro-convection to background meteorology. We examine here the effects of different plume injection height parameterizations on the model simulation of biomass burning long-range transport.…”
Section: Injection Heights Of Biomass Burning Emissionsmentioning
confidence: 99%
“…In earlier studies, ATHAM was employed to investigate volcanic eruptions (e.g., Oberhuber et al, 1998;Herzog et al, 1998;Graf et al, 1999;Textor et al, 2003) and wildfire induced convection (Trentmann et al, 2002Luderer et al, 2006). The dynamical core of ATHAM is such that it fully accounts for the effects of all tracers such as hydrometeors, aerosols and gaseous components on heat capacity and density.…”
Section: The Active Tracer High Resolution Atmospheric Model (Atham)mentioning
confidence: 99%